2014
DOI: 10.1016/j.biomaterials.2013.12.087
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of ectopic bone growth in critically-sized rat mandible defects by delivery of rhBMP-2 from kerateine biomaterials

Abstract: Absorbable collagen sponges (ACS) are used clinically as carriers of recombinant human bone morphogenetic protein 2 (rhBMP-2) to promote bone regeneration. ACS exhibit ectopic bone growth due to delivery of supraphysiological levels of rhBMP-2, which is particularly problematic in craniofacial bone injuries for both functional and esthetic reasons. We hypothesized that hydrogels from the reduced form of keratin proteins (kerateine) would serve as a suitable alternative to ACS carriers of rhBMP-2. The rationale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…It has previously been observed that release of rhBMP-2 from keratin hydrogels correlates with the rate of gel erosion [22, 23], suggesting a possible interaction between rhBMP-2 and keratin. Here, we determined an equilibrium binding value by a solid phase assay for rhBMP-2 and rhIGF-1 in order to (1) evaluate the strength of the interaction and (2) to determine if alkylation led to a change in the interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been observed that release of rhBMP-2 from keratin hydrogels correlates with the rate of gel erosion [22, 23], suggesting a possible interaction between rhBMP-2 and keratin. Here, we determined an equilibrium binding value by a solid phase assay for rhBMP-2 and rhIGF-1 in order to (1) evaluate the strength of the interaction and (2) to determine if alkylation led to a change in the interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, given the effects of keratin in burn wound healing [14], co-delivery of antibiotics may aid in reducing bacterial colonization to provide improved treatment and healing profiles [63]. As noted above, the higher binding affinity of rhBMP-2 for keratin may be advantageous compared to collagen in reducing ectopic bone growth, as we have recently reported [23]. Further, the ability to modulate keratin biomaterials that promote strong cell attachment while providing temporal control over delivery of therapeutic agents may lend keratin to other TERM applications that require more than a material alone.…”
Section: Discussionmentioning
confidence: 96%
“…Unlike collagen and some other naturally-derived proteins, to our knowledge humans do not produce enzymes that specifically degrade keratins (i.e., keratinases), which allows these materials to persist in vivo for longer periods of time. Lastly, in terms of controlled release, we have previously suggested 35,36 that release of therapeutic agents from keratin biomaterials is related to adsorption affinity of these materials to keratin and therefore release is not simply diffusion-mediated.…”
Section: Introductionmentioning
confidence: 99%
“…The current clinical strategy that uses supraphysiological doses of rhBMP-2 in the device helps to overcome the therapeutic threshold set by BMP-2 antagonists and inhibitors. Previous studies have focused on lowering loading concentrations by using alternative biomaterials to control the rate BMP-2 release from the carrier system [12, 18, 19, 51]. …”
Section: Discussionmentioning
confidence: 99%
“…This negative feedback mechanism provides a way to self-regulate endogenous BMP-2 levels under healing conditions and in clinical examples when rhBMP-2 is delivered exogenously as part of a synthetic bone graft. Considerable effort has been focused on the exploration of controlling the amount of rhBMP-2 delivered at the implant site either through alternative carrier systems [1820] or through the use of other delivery strategies [2123]. …”
Section: Introductionmentioning
confidence: 99%